2006
DOI: 10.1111/j.1360-0443.2006.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of hepatitis B virus infection among methamphetamine injectors: the role of sharing injection drug equipment

Abstract: Methamphetamine use has become increasingly prevalent in the United States. Our findings highlight the need for awareness of risks associated with injection drug use and sharing behaviors. Enhanced hepatitis B vaccination programs and educational campaigns that target methamphetamine injectors specifically, including those living in rural areas, should be developed and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
(11 reference statements)
1
24
0
Order By: Relevance
“…Reportedly, the remainder of the fentanyl in the patient vials was then administered to patients using the same syringe that was used to make the transfer. This mechanism of transmission by indirect syringe reuse, involving accessing contaminated vials or containers, has been well-documented in other viral hepatitis outbreaks associated with healthcare and injection drug use 17,18 . Epidemiologic and laboratory evidence indicated that the CRNA became infected, sequentially, with two different strains of HCV from chronically infected patients and subsequently transmitted to susceptible patients.…”
Section: Resultsmentioning
confidence: 95%
“…Reportedly, the remainder of the fentanyl in the patient vials was then administered to patients using the same syringe that was used to make the transfer. This mechanism of transmission by indirect syringe reuse, involving accessing contaminated vials or containers, has been well-documented in other viral hepatitis outbreaks associated with healthcare and injection drug use 17,18 . Epidemiologic and laboratory evidence indicated that the CRNA became infected, sequentially, with two different strains of HCV from chronically infected patients and subsequently transmitted to susceptible patients.…”
Section: Resultsmentioning
confidence: 95%
“…Injection of methamphetamine can lead to transmission of bloodborne pathogens when injection equipment is shared, as demonstrated in an outbreak of hepatitis B among methamphetamine users in Wyoming ( 27 ). A recent case series of 14 patients with MRSA necrotizing fasciitis found that 43% of the patients had current or past injection drug use ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early sexual behavior and frequent unprotected sex among heterosexual and homosexual users of methamphetamine result in higher rates of Hepatitis and HIV infection rates (Davis, Kalousek, & Rubenstein, 1970; Gorman, 2003; Greenwell & Brecht, 2003; Harkess, Gildon, & Istre, 1989; Hutin et al, 2000; Koester, Glanz, & Barón, 2005; Meyer, 2003; Molitor, Truax, Ruiz, & Sun, 1998; Urbina & Jones, 2004; Vogt et al, 2006). Methamphetamine use interferes with the efficacy of HIV medications and treatment (Anonymous, 2004; Boddiger, 2005; Jernigan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%